PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK LISTRIK DINAMIS DI SMA AMIR HAMZAH MEDAN - Erni Afdalita; Purwanto Purwanto (INPAFI (Inovasi Pembelajaran Fisika), 2015)
The purpose of this study was to determine the effect of cooperative learning model group investigation on learning outcomes in the subject matter physics dynamic electricity in SMA Amir Hamzah Medan. This type of research is quasi-experimental. The population of this entire class X SMA Amir Hamzah Medan. The sample in this study was taken as a random sampling of two classes. The instrument used  to determine student learning outcomes in the material dynamic electricity in the form of multiple-choice questions numbered 20. The t test hypothesis testing premises of the parties. Through the t test of the obtained results of student learning using learning model group investigation higher than conventional learning, so it is concluded that there is a significant relationship between the use of cooperative learning model group investigation on student learning outcomes. Keywords :  Cooperative learning model group investigation, learning outcomes.